BIOCHEMICAL STUDY OF NEW CHALCONE BASED ON CHROMONYL THIADIAZOLINE DERIVATIVE - ZAINAB KADHIM AL-KHAZRAGIE; HANAN A AL-HAZAM; SABAH ABBAS MALİK (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to synthesize and characterize a novel chalcone compound (ZH) derived from chromonyl thiadiazoline and to assess its biological activities, including antibacterial, antioxidant, and anticancer properties, as well as its fluorescence characteristics and DNA cleavage capability. Methods: The ZH molecule was synthesized and characterized structurally by elemental analysis, Fourier transform infrared (FT-IR) spectroscopy, multinuclear nuclear magnetic resonance (1H, 13C), and mass spectrometry. The acute toxicity was evaluated using Dixon’s up-and-down approach to ascertain the lethal dose 50% (LD50) value. The antibacterial efficacy was assessed using the minimum inhibitory concentration (MIC) method against Gram-positive bacteria (Streptococcus aureus and Bacillus) and Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa). The antioxidant activity was evaluated relative to the standard antioxidant butylated hydroxytoluene (BHT). The cytotoxic effect on MCF-7 breast cancer cells was assessed using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl tetrazolium bromide (MTT) test after 72 h of treatment. The compound’s fluorescence characteristics and DNA cleavage activities were examined. Results: The ZH compound demonstrated greater toxicity than its counterpart (2), as evidenced by a reduced LD50 value. It exhibited significant antibacterial efficacy, particularly against Gram-positive bacteria, with a MIC of 5 mg/mL. While ZH had notable antioxidant action, it was inferior to BHT (82%). The MTT assay demonstrated substantial cytotoxicity against MCF-7 cells, yielding an IC50 value of 45.54 μg/mL, which is markedly lower than that of the reference medication 5-Fluorouracil 5-FU (IC50 = 98.17 μg/mL). The molecule demonstrated significant fluorescence and efficient DNA cleavage activity. Conclusion: The synthesized ZH molecule has considerable bioactive properties, notably its antibacterial and anticancer efficacy, indicating substantial pharmacological potential. These findings underscore its significance for forthcoming advancements in medicinal chemistry and pharmaceutical design.